A Concluding Reflection - Richard Ruopp (Journal of Research in Rural Education, 1993)
This special issue of The Journal ofResearch in Rural Education is about a relatively new medium-telecommunication; aboutmessengerssendingand receiving in support of one another-teachers principally, but also students; and about a particular kind of messageproject-enhanced science learning. And the teacher essays set the context in rural settings.